Carbon in physical fractions and organic matter chemical composition of an acrisol after Amazon forest burning and conversion into pasture - Leal, Otávio A.; Dick, Deborah P.; Costa, Falberni S.; Knicker, Heike; de Carvalho Júnior, João A. [UNESP]; Santos, José C. (Sociedade Brasileira de Quimica (SBQ), 2019)
The aim of this study was to investigate impacts of Amazon Forest (AF) fire and conversion to pasture on carbon accumulation in particle size fractions and organic matter (OM) composition of an Acrisol. Soil samples were collected (0.00-2.00 m depth) in three sites: native AF (NAF); AF under natural regeneration for two years after burning (BAF); 23-years old Brachiaria pasture after AF burning (BRA). Assuming NAF area as reference, BAF and BRA areas showed negative carbon balance when carbon emitted to the atmosphere at AF burning is taken into account. Soil OM aromaticity and hydrophobicity, assessed via 13C nuclear magnetic resonance, in BRA and BAF were similar to that in NAF. Fire and post-fire land use altered the carbon distribution in sand, silt and clay along the soil profile and seem to have affected organo-mineral and OM self-assemblage interactions, since the relation between total soil carbon and carbon in clay was asymptotic in BAF and linear in NAF and BRA.
Keywords: 13C NMR; Aromaticity; Clay; Deep stocks; Saturation